Family Planning Knowledge and Attitudes of Childbearing Couples Regarding Reproductive Health with Husband's Participation - Lusianawati, Evalina Fransisca (HM Publisher, 2023)
knowledge about reproductive health and actively participate in family planning. Couples can plan pregnancies according to their wishes, avoid unwanted pregnancies, reduce the risk of reproductive health complications, and create an environment that supports optimal development of children. This study aimed to determine the relationship between family planning knowledge and attitudes of reproductive health couples regarding reproductive health with the husband's participation. This study is an analytical observational research with a cross-sectional approach. This study uses primary data obtained from the research subject interview process. A total of 211 research subjects took part in this study. In conclusion, there is no relationship between family planning knowledge and attitudes of couples of childbearing age regarding reproductive health with the husband's participation.